COMPARISON OF CLOPIDOGREL AND ACETOSAL IN THE PREVENTION OF RECCURENT ISCHEMIC STROKE AT DR. MOEWARDI REGIONAL GENERAL HOSPITAL - Dwi Kristiyowati, Anis; Andrajati, Retnosari; Bahtiar, Anton (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This study was conducted to determine the effect of clopidogrel on the prevention of recurrent stroke. Methods: This study used caseâ€“control study; data were taken from patient's medical record of DR. Moewardi Regional General Hospital in the period of January 2013 â€“ February 2017. Case group is a recurrent stroke patient receiving an acetosal or clopidogrel. The control group is a nonrecurrent stroke patient who receives an acetosal or clopidogrel. Results: During the period of study, the number of medical sample record data are 177 samples from the entire study subjects that met the inclusion and exclusion criteria, 50 medical records entered as subject of case study, 32 medical record samples was excluded because medical record data at the first stroke was gone (obselete), 35 medical record was excluded because medical record data at first stroke was not at of DR. Moewardi Regional General Hospital, 4 samples of medical records was excluded for using a combination of acetosal and clopidogrel, 55 samples of medical records as control subjects. Patients who use clopidogrel have a tendency to prevent recurrent stroke, but statistically not significantly different. This study shows that men tend to suffer more recurrent ischemic stroke (64.0%) than women. While in the control group of recurrent ischemic stroke of women (56.4%) more experienced the first stroke than men. Patients who had a stroke almost all had a history of hypertension (90.2%). Recurrent stroke patients in this study almost all had a history of hypertension. Bivariate analysis was showed that gender, history of diabetes mellitus (DM) and history of hypertension had an effect on recurrent stroke events. From the multivariate analysis, it was found that men had a risk of 2.328 for recurrent stroke (p=0.047), the history of DM had a risk of 3.975 times for recurrent stroke (p=0.016) and history of hypertension was 4.021 times for recurrent stroke (p=0.03)